Lymphocyte Glucose and Glutamine Metabolism as Targets of the Anti-Inflammatory and Immunomodulatory Effects of Exercise - Frederick Wasinski; Marcos F. Gregnani; Fábio H. Ornellas; Aline V. N. Bacurau; Niels O. Câmara; Ronaldo C. Araujo; Reury F. Bacurau (Hindawi Limited, 2014)
Glucose and glutamine are important energetic and biosynthetic nutrients for T and B lymphocytes. These cells consume both nutrients at high rates in a function-dependent manner. In other words, the pathways that control lymphocyte function and survival directly control the glucose and glutamine metabolic pathways. Therefore, lymphocytes in different functional states reprogram their glucose and glutamine metabolism to balance their requirement for ATP and macromolecule production. The tight association between metabolism and function in these cells was suggested to introduce the possibility of several pathologies resulting from the inability of lymphocytes to meet their nutrient demands under a given condition. In fact, disruptions in lymphocyte metabolism and function have been observed in different inflammatory, metabolic, and autoimmune pathologies. Regular physical exercise and physical activity offer protection against several chronic pathologies, and this benefit has been associated with the anti-inflammatory and immunomodulatory effects of exercise/physical activity. Chronic exercise induces changes in lymphocyte functionality and substrate metabolism. In the present review, we discuss whether the beneficial effects of exercise on lymphocyte function in health and disease are associated with modulation of the glucose and glutamine metabolic pathways.